Analysis of Bukit Menoreh Durian Fruit as a Culinary Tourism Potential in Kokap District - Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2022)
The potential for durian culinary tourism in Bukit Menoreh, Kokap District, Kulon Progo Regency. But in its development it still has many obstacles, both internal and external constraints. The purpose of this study is to analyze the level of feasibility of developing culinary tourism. The research method used is a descriptive research method. The population and research sample are individuals who are in institutions related to the development of the Kokap sub-district. The sampling technique in this study was purposive sampling and quota sampling by taking 1 key informant from each developer agency. Data collection techniques used are observation, interviews, documentation and questionnaires. The conclusion from this study is that Kokap District has the potential to be developed as an educational tourism object and the constraints experienced by its development can be minimized.